Equity home bias : an ownership, governance, and globalization perspective. - Ng, Delvin Teck Siang. (2008)
The strong bias in favor of domestic equities is a well-documented characteristic of international investment portfolios, and it remains an important yet unresolved puzzle. We examine equity home bias in a different perspective. Unlike traditional papers which focused on barriers to international investment as the cause of home bias, this paper seeks to verify if home bias is caused by a preference for domestic securities instead. We highlight the role of governance, and the relationship between governance and corporate ownership concentration in this approach. Our results suggest that insider ownership plays a significant role in directly affecting the level of home bias in a country. Governance does affect the level of home bias in a country as well, but indirectly through its impact on insider ownership. In addition, we offer some insights into understanding the equity home bias puzzle by examining if any of the prominent globalization trends such as increase in free trade, the advent of the internet, and the rise of emerging markets have affected equity home bias. Our findings suggest that internet, and subsequently insider ownership, play a highly significant role in shaping equity home bias as well.